Analisis Faktor-Faktor yang Memengaruhi Perilaku pengguna Messenger ABC dalam Penerimaan Informasi pada Lembaga XYZ dengan Menggunakan The Unified Theory of Acceptance and Use of Technology (UTAUT) - Ami Fajar Hikmah; Ari Kusyanti; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Internet is one of the information technology that can facilitate user to find information and communicate with other. The most popular service of internet is instant messenger. LINE is the most favourite application for user. LINE messenger is an application that provide free messaging, free call and video call. One of the example of LINE messenger user is Eksekutif Mahasiswa Sistem Informasi of Brawijaya University (EMSI UB). EMSI is an executive institution in the Faculty of Computer Science Brawijaya University. In use of LINE in the EMSI UB have a problem, one of the problem is evidence of important conversations with other user screenshoot by other users and the results of conversations are disseminated to other users as well. This research purpose to determine about relationship between independent variables and dependent variables and knowing about factors that can affect LINE user about receiving information on EMSI UB. This research use The Unified Theory Of Acceptance and Use Of Technology (UTAUT), this model developed by Venkatesh et al. (2003) and all of result questionnaire processed by linear regression analysis. The samples used in this research is 100 user through an online questionnaire. The results of this research show that Effort Expectancy, Social Influence, Trust and Privacy variables have a significan influence on Behavioral Intention. There are two factors that have no significant influence on Behavioral Intention is Performance Expectancy and Faciliting Condition.